2009
DOI: 10.3399/bjgp09x419529
|View full text |Cite
|
Sign up to set email alerts
|

Brief intervention addressing excessive cannabis use in young people consulting their GP: a pilot study

Abstract: SettingSeven family practices in Switzerland. MethodThe team collaborated with GPs and young people to develop the intervention. Seven GPs piloted its use in their consultations. Patients aged 15 to 24 years consulting for any health problem were recruited before the consultation. Cannabis use, other substance use, and their psychosocial correlates were assessed with a short confidential questionnaire administered before the consultation and 1 month later. GPs, staff, and patients were asked to comment on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
2
29
0
3
Order By: Relevance
“…The pilot study in 7 practices was successful in showing that the intervention could be used during the consultation to address binge drinking and excessive cannabis use. 30 The reduction in the proportion of excessive substance users 1 month after exposure to the brief intervention in the pilot practices, consistent with that reported in trials involving adults, 20 provided support for the validity of our approach. 30 During the training, the practitioners were instructed to go through some or all of the 5As depending on their assessment of the patient's need and motivation to change.…”
Section: Interventionsupporting
confidence: 64%
See 3 more Smart Citations
“…The pilot study in 7 practices was successful in showing that the intervention could be used during the consultation to address binge drinking and excessive cannabis use. 30 The reduction in the proportion of excessive substance users 1 month after exposure to the brief intervention in the pilot practices, consistent with that reported in trials involving adults, 20 provided support for the validity of our approach. 30 During the training, the practitioners were instructed to go through some or all of the 5As depending on their assessment of the patient's need and motivation to change.…”
Section: Interventionsupporting
confidence: 64%
“…Thus, the baseline surveys were collected in sealed envelopes before the consul-tation and not made available to the physicians to help them identify patients at risk. 30 As a result, all young people who consented to participate were included in the trial, not only those who reported excessive substance use at baseline.…”
Section: Baseline Patient Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…À l'échelle d'une population, la prise en charge des addictions concernant le tabac, l'alcool, le cannabis et les opiacés relève essentiellement des médecins généralistes (MG) [1][2][3]. En France, selon le Baromètre santé 2009 [4], près de deux tiers des MG sont consultés par un usager dépen-dant aux opiacés dans l'année, et 59 % par un usager de cannabis.…”
Section: Introductionunclassified